International Biological Flora: Nervilia nipponica. (11th June 2021) - Gale, Stephan W.; Maeda, Ayako; Miyashita, Ayana; Sugiura, Daisuke; Ogura‐Tsujita, Yuki; Kinoshita, Akihiko; Fujimori, Shohei; Hutchings, Michael J.; Yukawa, Tomohisa
Abstract: This account presents information on all aspects of the biology of Nervilia nipponica Makino ( mukago‐saishin ) that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the International Biological Flora : distribution, habitat, communities, responses to biotic factors, responses to the environment, structure and physiology, phenology, floral and seed characters, herbivores and disease, history, conservation and global heterogeneity. Nervilia nipponica is a small, stoloniferous, seasonally dormant herb that grows in the understorey of evergreen forests in the humid subtropical zone of central and western Japan, with a few outlying populations on Jeju Island in South Korea. Its northern extent is defined by the 0°C winter isotherm, and its occurrence is also limited by site aspect and incline. It is a weak competitor that occupies species‐poor microsites in which bare ground and leaf litter predominate. Plant numbers tend to decline as percentage ground cover of surrounding understorey vegetation increases. The inflorescence sprouts from a short‐lived, subterranean tuber in late spring and leaf‐flush occurs after fruit‐set. However, most tubers do not flower in any one annual growth cycle. Long‐term monitoring of individually marked plants suggests that tubers are resource‐limited and that flowering constrains future genet growth. Nervilia nipponica is exclusively autogamous and has a strong capacity for vegetative propagation. The species is genetically depauperate but exhibits significant differentiation between populations, which comprise clonal clusters in phalanx formation. The level of mycorrhizal infection differs between plant parts and through successive phenological stages. Stable isotope signatures indicate that the species is partially mycoheterotrophic, with fungal partners supporting growth particularly at lower light intensities. Despite this, falling light availability associated with forest succession can lead to population decline. Populations tend to be small and prone to extirpation, but the species is probably under‐recorded as a result of its ephemeral emergence above‐ground and inconspicuous habit. Management interventions likely to benefit the species at the site level include thinning dense forest canopy and removing encroaching ground cover. Abstract : This account presents information on all aspects of the biology of Nervilia nipponica, a rare geophytic herb native to Japan and Korea, relevant to understanding its ecological characteristics and behaviour. It is a small, seasonally dormant, partially mycoheterotrophic herb that grows in the understorey of evergreen forest, but it is a weak competitor that declines as surrounding ground cover increases.